Conduction transportation from graphene to an insulative polymer medium: A novel approach for the conductivity of nanocomposites - Zare Yasser; Munir Muhammad Tajammal; Rhee Kyong Yop; Park Soo-Jin (Nanotechnology Reviews, 2024)
Some models have been proposed for the electrical conductivity of graphene-filled nanocomposites, but they have not reflected the characteristics of an imperfect interphase surrounding the graphene nanosheets. In this article, the size and conductivity of an imperfect interphase are used to develop a model for conductivity of the graphene/polymer system. Also, “Y,” the degree of conduction transfer through an imperfect interphase, is expressed as graphene dimensions and interphase conductivity to define the effective converse aspect ratio and effective filler portion in the samples. The developed model for nanocomposite conductivity is examined by the experimental data of some samples. Furthermore, the influences of various factors on “Y,” percolation onset, and nanocomposite conductivity are investigated. Thin and large nanosheets, poor filler conductivity, and high interphase conductivity produce a high “Y.” Likewise, “Y” and graphene volume portion (φf)({φ }_{\text{f}}) significantly govern the conductivity of samples. Y = 9 and φf{φ }_{\text{f}} = 0.03 yield the highest nanocomposite conductivity of 16 S/m, while Y < 2 or φf{φ }_{\text{f}} < 0.022 cannot improve the conductivity of samples.